QARAQALPAQ XALÍQ JUMBAQLARÍNDAǴÍ AYÍRÍM ÚY BUYÍMÍ ATAMALARÍ HAQQÍNDA - Abishov, G.M.; Sársenbaeva, B.S. (SCIENCE and SOCIETY, 2024)
In this article, the riddles, which are one of the Karakalpak folklore works, are learned. The meanings of the names of the household items used in it, their places of use, the problem of the connection between the term and the riddles are shown on the example of Karakalpak folk riddles. Also, the cases are mentioned these terms which used or not used at the present time.